Surgical Results of Phacoemulsification Performed by Residents: A Time-Trend Analysis in a Teaching Hospital from 2005 to 2021 - Jiahn-Shing Lee; Chiun-Ho Hou; Ken-Kuo Lin (Journal of Ophthalmology)
Purpose. To report a long-term trend of surgical results of phacoemulsification performed by residents in a teaching hospital. Methods. This study analyzed 1,409 consecutive cases of phacoemulsification performed by residents under a single supervisor from July 2005 to March 2021. The 15.75-year period was divided into seven equal intervals for time-trend analysis. Main Outcome Measures. Rates of completion and complications were collected to assess the surgical results. Results. The overall completion rate was 60.5% (852/1409), and the intraoperative complication rate was 14.5% (204/1409). The completion rates from the first to the seventh interval were 44.7%, 54.2%, 60.6%, 50.6%, 65.1%, 72.5%, and 81.8%, respectively. The completion rate improved significantly with time, mainly in the steps of anterior capsulorhexis and nucleus emulsification. The intraoperative complication rates from the first to the seventh interval were 27.4%, 20.4%, 14.0%, 11.8%, 8.2%, 9.6%, and 7.3%, respectively. The complication rate also decreased significantly with time, mainly in the steps of anterior capsulorhexis, nucleus emulsification, and cortex removal. The major complications included anterior capsulorhexis tear (n = 95), vitreous loss (n = 40), iris damage or prolapse (n = 36), and posterior capsule tear without vitreous loss (n = 29). There was a significant improvement of surgical results with the level of residency in the completion rate but not in the complication rate. Conclusions. With a long-term evolution in the surgical training curriculum, it is possible to reach a goal of both higher completion and lower complication rates of resident-performed phacoemulsification.